2020
DOI: 10.20944/preprints202007.0398.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New SARS-CoV-2 Infection in a Pet Cat with Severe Lung Disease in Italy

Abstract: The pandemic respiratory disease COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in Wuhan in December 2019 and then spread throughout the world; Italy was the most affected European country. Despite the close pet-human contact, little is known about the predisposition of pets to SARS-CoV-2. Among these, felines are the most susceptible. In this study, a domestic cat with clear symptoms of pneumonia, confirmed by Rx imaging, was found to be infected by SARS-CoV-2 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Previously, Musso et al showed SARS‐CoV‐2 infected cat in Italy displayed pneumonia, however, there is no evidence for B.1.17. variant 24 …”
Section: Discussionmentioning
confidence: 99%
“…Previously, Musso et al showed SARS‐CoV‐2 infected cat in Italy displayed pneumonia, however, there is no evidence for B.1.17. variant 24 …”
Section: Discussionmentioning
confidence: 99%